Biomass conversion and upgrading over carbon catalyst - Chen, Xiaoping (2018)
Biomass conversion and upgrading are promising solutions for energy shortage and environment problems. Located in Southeast Asia, Singapore is surrounded by abundant biomass resource in its neighboring countries. However, most of the biomass feedstock is underutilization. Cellulose, which represents the most abundant biomass resource, has been examined over noble metal supported carbon catalyst as an example of biomass conversion. As a Johnson Matthey (JM) supported program, we examined cellulose hydrogenation over Pt/AC produced from JM by the trial-and-error method. After tuning the reaction conditions, a sorbitol yield up to 25% is obtained. We also proposed a novel and effective catalyst optimization method which can further improve the sorbitol yield to 50% by further reducing the Pt/AC in ethylene glycol. This catalytic performance improvement is attributed to the effect of particle size according to XRD and TEM results. CV scans of the Pt/AC indicate that the decline of platinum’s oxidation and reduction activity after EG treatment may suppress the side reactions during cellulose hydrogenation, hence improve sorbitol yield. Ruthenium has been proved as an ideal catalyst in biomass conversion, especially for cellulose hydrogenation. However, studies of such reactions are extremely time-consuming due to the numerous side reactions and the complexity of interactions among reaction parameters. In this work, we introduced multivariate analysis method for the study of cellulose hydrogenation. The effect of temperature, hydrogen pressure, catalyst amount and ruthenium loading were comprehensively explored based on a response surface design (RSD). Among all the 26 hydrogenation reactions, the highest sorbitol yield of 71.9% was obtained. The reaction data was then used to produce a regression model which shows strong statistical significance and high accuracy. Though this model, we evaluated the effectiveness of all the reaction parameters. It was found that ruthenium loading and temperature were the two main driving forces for sorbitol yield. High sorbitol yield could only be obtained while ruthenium loading and temperature were well tuned. The synergistic effects among reaction parameters were well presented with the help of contour plots and surface plots generated from the model. Lastly, a prediction formula according to the reaction data was constructed to predict the sorbitol yield under other reaction conditions. Sorbitol, which is the main product of cellulose hydrogenation, has been examined over sulfonated carbon catalysts as an example of biomass upgrading. The sulfonated carbon catalysts show high catalytic activity towards the synthesis of isosorbide from sorbitol, with a yield up to 60% with negligible performance loss for five consecutive runs. The sulfuric groups are identified as the main active sites for sorbitol dehydration. The physical and chemical properties of the catalysts are evaluated by advanced and extensive characterization techniques, such as XRD, TEM, SEM, BET, FTIR, EA, EDAX, TGA and Raman spectroscopy.